TWO ADJACENT VOWELS IN PAGU AND THEIR ALTERNATING WORD STRESS PLACEMENT - Perangin Angin, Dalan Mehuli (International Journal of Humanity Studies (IJHS), 2020)
Some diphthongs in Pagu, rather than being pronounced as a single syllable in a normal/rapid speed of speech, can alternate to appear in two different adjacent syllables when pronounced in a slow speech. In Pagu, the speed of speech affects the words syllable number and word stress placement. The previous study suggests that word stress in Pagu is placed on the penultimate syllable. This paper will discuss word stress placement in Pagu in two different speed of speech (normal and slow) as well as two adjacent vowels as affected by the speed and their position in the word. This sheds a light on the behaviors of two adjacent vowels in the stress placement area i.e. whether they are different vowels they can alternate between a diphthong or two separate vowels in two different syllables and when they are identical they cannot be separated into two different syllables when occur in the final position.